The effect of work Stress on Mental and Its Implication for Police Behaviour in Indonesia - Horas Marasi Silaen; Adrianus Eliasta Sembiring Meliala; Vita Mayastinasari; Novi Indah Earlyanti (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2025)
This quantitative study investigates the impact of work stress on the mental health and subsequent behavior of Indonesian police officers. Utilizing a survey method with a sample of 400 officers, the research employs a structural equation modeling (SEM) approach to examine the relationships between work stress, mental health, and police behavior. The findings reveal a significant direct effect of work stress on both mental health and police behavior. Importantly, mental health mediates the relationship between work stress and behavioral outcomes. High work stress significantly predicts poorer mental health, which, in turn, is strongly associated with less effective police behavior. The study utilizes established scales to measure these constructs, including indicators related to emotional, intellectual, physical, and interpersonal responses to stress, alongside measures of mental health encompassing self-image, mood, relationships, and future outlook, and police behavior assessed through dimensions of legitimate force, adherence to procedures, and community interaction. While the initial SEM model exhibited fit issues, modifications improved the model fit, strengthening the key relationships. This research underscores the critical role of mental health in influencing police conduct and highlights the need for interventions aimed at mitigating work stress and improving the mental well-being of Indonesian law enforcement personnel. Such interventions should include coping skills training, emotional intelligence development, workload management, and improvements to organizational support systems.